Iron Cage Birokrasi Pendidikan: Suatu Analisis Sosiologis - Siti Ikramatoun; Khairul Amin; Darwin; Halik (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2021)
This article aims to describe the education bureaucracy as a tool to achieve the objectives of education through a qualitative approach to the literature study model. The data in this paper is sourced from relevant literature and the author's experience while active in educational activities. The results of this study indicate that the bureaucracy in the form of educational administration has changed to an iron cage that shackles the educational activity itself. The delivery of education loses its orientation and turns into ceremonial routines to meet the demands of the bureaucracy. Various training, capacity building, and teacher competence have been done, but they have not significantly changed the face of education. Iron cage bureaucracy makes teachers "appear" to be developing their competence, but in fact, they are meeting the demands of the bureaucracy. Education must come out of the iron cage bureaucracy by reducing all administrative aspects that bind the noble activities of education. Bureaucracy is a human creation, so bureaucracy should be subject to humans and not humans who are subject to the will of the bureaucracy. Artikel ini bertujuan mendeskripsikan birokrasi pendidikan sebagai alat untuk mencapai tujuan penyelenggaraan pendidikan melalui pendekatan kualitatif dengan model studi literatur. Data dalam tulisan ini bersumber dari literatur yang relevan dan pengalaman penulis selama aktif dalam aktivitas pendidikan. Hasil kajian menunjukkan bahwa birokrasi dalam bentuk administrasi pendidikan berubah menjadi “kerangkeng besi” yang membelenggu aktivitas pendidikan itu sendiri. Penyelenggaraan pendidikan kehilangan orientasinya dan berubah menjadi rutinitas seremonial demi memenuhi tuntutan birokrasi. Beragam pelatihan dan peningkatan kapasitas maupun kompetensi guru dalam dunia pendidikan telah dilakukan, namun belum mampu mengubah wajah pendidikan secara signifikan. Kontrol birokrasi membuat para guru “terlihat” sedang mengembangkan kompetensinya, padahal sejatinya sedang memenuhi tuntutan birokrasi. Untuk itu, pendidikan harus keluar dari “jerat birokrasi” dengan cara mereduksi semua aspek administratif yang membelenggu aktivitas mulia pendidikan. Birokrasi adalah hasil ciptaan manusia, maka seharusnya birokrasi tunduk pada manusia dan bukan manusia yang tunduk pada kehendak birokrasi.